Association between shift work and cognitive performance on the Trail Making Test in emergency department health officers. (11th March 2021) - Sun, Jessica; Stewart, Patrick; Chiew, Angela; Becker, Therese; Siu, William; Varndell, Wayne; Chan, Betty S
Abstract: Objective: Shift work has been proposed to disturb alertness and decrease cognitive efficiency. However, studies so far have had varied findings. The aim of the present study was to compare cognitive function following shifts at different times of the day in an Australian ED context. Methods: A prospective, self‐controlled observational study was conducted on medical and nursing staff at a tertiary referral centre and regional hospital ED. Participants were required to complete the Trail Making Test (TMT), a neurocognitive test consisting of two parts (TMT‐A and TMT‐B), at baseline (at the start of the day) and at the end of their shift (day, evening or night). Related samples Wilcoxon signed‐rank tests were used to compare post‐shift TMT performance to baseline in medical and nursing staff. Results: Over a 5‐month period, 140 ED staff were recruited including 109 doctors and 31 nurses. After a night shift, medical staff ( n = 85) and nursing staff ( n = 29) took longer to complete the TMT‐B by 3.4 s ( P < 0.001) and 7.1 s ( P = 0.01), respectively, compared to baseline. Post‐evening shift, medical staff ( n = 59) took longer to complete the TMT‐A by 0.3 s ( P = 0.02). Conclusions: Night shift work was associated with a longer TMT time. This may indicate a decrease in cognitive performance, in particular, visual attention, processing speed, task switching and executive function and may implicate the quality of care for patients and worker safety. Abstract : Night shift work was associated with a longer trial‐making test time. This may indicate a decrease in cognitive performance and may have an implication on the quality of care for patients and worker safety.